The Ritual of Cooperation and the Routine as a Tool for Shaping Social and Civic Competences – Based on the Thoughts of Richard Sennett - Iwona Paszenda (Studia z Teorii Wychowania)
The subject of the article is the problem of the discrepancy between the actual educational practice in schools and the official policy and declarations regarding shaping social and civic competences, characterized, inter alia, by the ability to cooperate. The aim of the article is to try to answer the question about the causes of weakening the ability to cooperate in the everyday functioning of people and institutions. The answer to this question is analyzed on the basis of the source texts of Richard Sennett, an American sociologist who devoted a lot of space to this problem in his works. In the first part of the article, the author describes the problem of the condition of modern man. In the second part, she presents the problems of changes taking place in today's world that cause the "corrosion of character" of human. In the third part, she discusses the issue of cooperation ritual and routine, which have the power to educate. The last part of the article, she presents an attempt to answer the question about what one needs / what one can to be changed in contemporary education, so that the development of competencies important from the point of view of functioning in the contemporary world has become an essential tool for education and upbringing.